Prevalence of Toxoplasmosis among Aborted Women and Immunohistochemical Evaluation of their Placenta - Kawther A. M. Al-Mussawi (Journal of Global Pharma Technology, 2016)
Toxoplasmosis is one of the zoonotic diseases caused by the obligate intracellular protozoan Toxoplasma gondii, which is associated with spontaneous abortion in infected pregnant women. In the present study, the sera of 228 first-trimester aborted women were screened for anti-Toxoplasma IgG and IgM antibodies, and the infection was further assessed in the blood and placenta of positive and negative cases by molecular methods. The results revealed that 47.4% of aborted women were sero-positive for toxoplasmosis (AT) by the latex agglutination test, while 52.6% were negative (NT). It was also found that 74.1% of AT cases were positive for IgG, while 25.9% were positive for IgM. In addition, the examined AT cases showed the amplified DNA fragment of the parasite, while it was not observed in NT samples. The placenta of molecularly diagnosed AT and NT cases were subjected for immunohistochemical expression evaluation for T-bet, GATA-3, FOXP3, IL-17, CD8, CD68 and perforin. A significant increased expression of T-bet, IL-17, CD8, CD68 and perforin was observed in AT cases compared to NT cases. In contrast, FOXP3 showed a significant decreased expression in AT cases, while no significant difference was observed for GATA-3. In conclusion, toxoplasmosis is an important risk factor for spontaneous abortion, which was associated with abnormal expression of some immunological markers in placenta.Keywords: Toxoplasmosis, Abortion, Prevalence, Immunohistochemical expression.